Colour atlas of tropical dermatology and venerology (Springer-Verlag, 1994)
The contents have been arranged, as far as possible, on the basis of aetiology, with chapiters on diseases due to infectious organisms, parasites, venomous animals, and genetic, nutritional, chemical and physical factors. The aims of this atlas is to provide clear guidance and a source of quick and easy reference for all physicians dealing with patient suffering from exotic skin diseases and for medical staff working in tropical and sub-tropical regions